Damage of soils by military actions and prospects оf their research and restoration - Babikova, Kateryna; Mikhalevska, Tetiana; Bereza-Kindzerska, Ludmyla; Bazhay-Zhezherun, Svitlana (My University, 2023)
The types of negative impact of military actions on the ecological condition of soils are considered. Directions and sequence of soil condition study in the post-war period are determined. Stages and methods of restoration of war-damaged soils are outlined

Розглянуто види негативного впливу військових дій на екологічний стан ґрунтів. Визначено напрямки і послідовність дослідження стану ґрунтів у пост воєнний період. Окреслено етапи та методи відновлення пошкоджених війною ґрунтів
Keywords: soils; ґрунти; military actions; військові дії; environmental monitoring; екологічний моніторинг; soil restoration; відновлення ґрунтів; кафедра технології оздоровчих продуктів